A Study of the Process and Types of Deindustrialization in the Visegrád Countries - Hegyi-Kéri, Ágnes (Theory, Methodology, Practice – Review of Business and Management, 2016)
My goal in this article is to analyze the process of deindustrialization from the aspect of the labor market. Accepting the definition of the relevant literature, I define deindustrialization as a decline in the number of workers employed in industry and a drop in their ratio on the labor market. My experimental question is whether deindustrialization was present in the Visegrád countries between 1993 and 2015, and if so, what kinds can be identified. In this work I merge the observations of developed countries regarding deindustrialization and also expand upon the methodology for defining the types of deindustrialization.